Whiteness as currency: colorism in contemporary fiction of the Anglophone Caribbean and the Cape - Smit, Brittani Reniece (Department of English Language and Literature, 2019)
People of colour are often expected to meet externally determined standards of whiteness in exchange for privileges and benefits. The specific details regarding how those standards are determined vary based on context and depend on a variety of socio-historical factors. Regardless of the context, meeting these standards typically requires rejection of indigenous ways of being in favour of foreign ideals. Colorism, which is discrimination based on skin tone, plays a significant role in determining the success of attempts at assimilation because of the long history of preferential treatment associated with light skin throughout slavery and colonialism which persists today. This dissertation is an investigation of the complex interplay between race, colour, class and gender in contexts characterised by colorist hierarchies in the shadow of the British Empire. It focuses primarily on texts written by and about women and foregrounds gendered experiences of race in the Cape region of South Africa and Anglophone Caribbean, highlighting the unique experiences of women of colour in relation to colorism and intersectional class-based discrimination in post-colonial/apartheid spaces. I examine the cultural, social and psychological impact of the classist and colorist ideologies born out of the similar histories of colonialism, slavery and indentured servitude in the Anglophone Caribbean and South Africa, specifically through the lens of contemporary literature written by authors whose work displays a particular sensitivity to these intersections. I am especially interested in the paradoxical relationship between derision and desire that accompanies aspirations towards whiteness and appropriations of European and particularly British cultural norms for people of colour in these contexts. The persistence of this tension as a trope in post-colonial/apartheid spaces resists the narrative of progression suggested by the political rhetoric of multicultural unity espoused by the governments of South Africa and the Caribbean and the retrospective writing analysed in this project functions as a palimpsest belying the optimism of current times.